PENGARUH PENGENDALIAN INTERNAL BISNIS ONLINE TERHADAP PENCEGAHAN FRAUD - Febriyanti Pungkasih Rahadi; Sri Sasmita (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
The development of online business in Indonesia is very fast. The rapid development of this online business cannot be separated from the development of internet technology in Indonesia. However, this does not guarantee that all online businesses have implemented effective and efficient internal controls in their business. To deal with the problem of online business fraud fraud, proper monitoring is needed within the online business internally The purpose of writing this journal is to be able to find out online business information and to find out the effect of online business internal control on fraud prevention and detection in the development of the world economy in Indonesia, especially in the field of online business. In preparing this journal, using descriptive qualitative methods using analysis, data, and utilizing existing theories as supporting materials. This journal uses secondary data sources obtained from other research journals and is based on the